Helping midwives support families who require non-therapeutic infant male circumcision. (2nd April 2022) - Whittaker, Paula J; Shaw, Catherine; Strange, Joshua; Gollins, Helen
Abstract : In the UK, the majority of non-therapeutic infant male circumcisions for religious or cultural reasons are performed by private providers in community settings. There have been reports of unsafe practices by some unregulated private providers. The implementation of a voluntary quality assurance process in one region in northwest England has been associated with a decrease in paediatric surgical admissions of infant boys admitted following complications of circumcision in the community. Voluntary quality assurance is a feasible option to implement quality improvement for services outside clinical governance systems. The quality assurance process provides a valuable resource for midwives to signpost families to safely practising providers, potentially reducing the risk of harm to children resulting from families using unqualified providers and safeguarding infant boys from harm becuase of poor practice.